2019
DOI: 10.1021/acs.joc.9b00040
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Sensing in Aqueous Media Using Porphyrin–Curdlan Conjugates: An Allosteric Signal-Amplification System

Abstract: A series of porphyrin−curdlan conjugates 1−5 of varying degree of substitution (DS) were synthesized to examine their morphological features, chiroptical properties, and oligosaccharide sensing in aqueous media, particularly for tetrasaccharide acarbose, which is a drug to treat type-2 diabetes. The random coil state of compounds 1−5 in DMSO becomes the globule curdlan−saccharide coaggregate upon interaction of acarbose in aqueous DMSO solution to induce various circular dichroism (CD) responses. The high coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…In contrast to the morphology of native Cur, as shown in Figure 2b, the AFM images of TPE-Cur 0.13 represent dotted structureless globules with a diameter of 111 nm and a height of 3 nm (see the analysis data in Figure S8), as was the case with other chromophore-modified Curs. 48,49 This indicates that modifying TPE can also induce random coil-to-globule conversion, and the reversible process is rather general in glucan chemistry. The hydrodynamic diameter (d h ) of the globule in the aqueous solution was estimated as 52 nm using dynamic light scattering (DLS), as shown in Figure 6b (black line, vide infra).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the morphology of native Cur, as shown in Figure 2b, the AFM images of TPE-Cur 0.13 represent dotted structureless globules with a diameter of 111 nm and a height of 3 nm (see the analysis data in Figure S8), as was the case with other chromophore-modified Curs. 48,49 This indicates that modifying TPE can also induce random coil-to-globule conversion, and the reversible process is rather general in glucan chemistry. The hydrodynamic diameter (d h ) of the globule in the aqueous solution was estimated as 52 nm using dynamic light scattering (DLS), as shown in Figure 6b (black line, vide infra).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In general, glucans containing native (unmodified) Cur exhibit reversible denaturing/renaturing processes to form an extended string in DMSO and a triplex in aqueous solutions (see Figure d). In contrast, we have demonstrated that chromophore-modified Curs exhibit different morphological changes in the reversible transition process. For instance, porphyrins and some π chromophores, such as circular dichroism (CD) reporters, were conjugated with Cur (Figure b). ,,, These modified Curs form a globule in aqueous solutions; the renaturing is particularly significant for oligosaccharide sensing in aqueous media. As shown in Figure e, upon random coil-to-globule conversion, the random-coiled Cur in DMSO transformed into a Cur-saccharide coaggregation by incorporating a target oligosaccharide molecule into the globular hydrogen-bonding network.…”
Section: Introductionmentioning
confidence: 99%
“…Metal chelation was set as the final step because transition metals can be easily complexed to the core of tetrapyrrole compounds at mild condition. [38][39][40] The final products of porphyrin and Pc analogues were acquired after HPLC separation and then freeze-dried, and before usage the content of each compound was determined according to levels of metal determined by using inductively coupled plasma-optical emission spectrometry (ICP-OES). All the compounds where possible are characterized by methods such as electrospray ionization mass spectrometry (ESI-MS),…”
Section: Design and Synthesis Of The Zn Pc And Porphyrin Compoundsmentioning
confidence: 99%
“…23−27 From an analytical perspective, synthetic chemosensors are particularly attractive because of their high sensitivity, stability, and low cost. For example, cyclodextrins, 28 porphyrins, 29,30 calixarenes, 31 and boronic acids 12,32−34 have been utilized as receptors for saccharides.…”
mentioning
confidence: 99%
“…Consequently, biological recognition elements have been employed in a number of biosensors. , In addition to biosensors, various chemosensors utilizing synthetic receptors have been used for carbohydrate recognition and sensing. From an analytical perspective, synthetic chemosensors are particularly attractive because of their high sensitivity, stability, and low cost. For example, cyclodextrins, porphyrins, , calixarenes, and boronic acids , have been utilized as receptors for saccharides.…”
mentioning
confidence: 99%